Neural Correlates of Empathy in Boys With Early Onset Conduct Disorder - von Polier, Georg G.; Greimel, Ellen; Konrad, Kerstin; Großheinrich, Nicola; Kohls, Gregor; Vloet, Timo D.; Herpertz-Dahlmann, Beate; Schulte-Rüther, Martin (Frontiers in Psychiatry, 2020)
Background: A deficit in empathy has repeatedly been described in individuals with conduct disorder (CD), and in particular in those with callous unemotional traits. Until now, little is known about the neural basis of empathy in children and adolescents with early onset conduct disorder. The aim of this study was to examine neural responses during empathizing in children and adolescents with CD with a task that allowed to differentiate between the judgment of the emotional states of other people and the own emotional response to other people´s emotional state. Moreover, we investigated associations of callous-unemotional traits and neural activations during empathizing. Methods: Using functional magnetic resonance imaging (fMRI) we investigated 14 boys with early onset CD and 15 typically developing (TDC) age matched controls between 8 and 16 years of age. Happy and sad faces were presented, and participants were asked to either infer the emotional state from the face (other-task) or to judge their own emotional response (self-task). A perceptual decision on faces was used as a control task. Individual empathic abilities and callous unemotional traits were assessed. Results: During the other task, TDC boys showed significantly larger right amygdala responses than CD boys. Higher empathic abilities (as assessed with the BIE) were associated with higher responses in the right amygdala within the CD boys and across the entire sample. Moreover, callous-unemotional traits were negatively related to the BOLD-response in the right amygdala. CD boys showed larger responses in the dorsal and ventral medial prefrontal cortex across tasks and increased activation in dorsal medial prefrontal cortex specifically during the self-conditions. Conclusions: The data emphasize the important role of the amygdala in empathy related emotional processing. Diminished amygdala responses and their association with low empathy and high callous unemotional traits suggest a pivotal influence of impaired amygdala processing in early-onset CD, in particular for deficits in empathic behavior. Elevated response in the medial prefrontal cortex in boys with CD point towards increased demands on self-referential processing to solve empathy tasks, potentially pointing at a more cognitive biased processing strategy in this patient group.